FINANCIAL PLANNING TOWARDS FINANCIAL HEALTH OF THE FAMILY - Kusumawardani, Media (LPPM Univ. Ibn Khaldun Bogor, 2022)
There are still few Indonesian people who do financial planning. This phenomenon also occurs in the people of Muara Penimbung Ilir village. The people of Muara Penimbung Ilir village do not understand the benefits of financial planning, especially family finances. Based on these problems, the implementation of this service activity has the aim of increasing public understanding of the importance of family financial planning. The method of implementing the service is done by providing material, presenting a reading book entitled Family Financial Planning, and a family planning diary. The result of community service activities is public knowledge in the financial sector and motivates the community to carry out family financial planning.